Daya Terima Formula Ikan Haruan Dan Formula Ayam Pada Balita Stunting Di Wilayah Kerja Puskesmas Martapura Timur Kabupaten Banjar Kalimantan Selatan - magdalena, magdalena (Jurnal Skala Kesehatan, 2024)
Stunting is one of the nutritional problems caused by malnutrition and is related to insufficient nutrition in the past. The 2021 Indonesian Nutrition Status Study (SSGI) South Kalimantan Province ranks 6th with a presentation of 30.0%. Data from the Banjar District Health Service for March 2023 at the East Martapura Health Center showed that there were 188 stunted toddlers. In Central Malay Village, there are 11 stunted toddlers. According to the Minister of Health's Decree ≤ 20% is said to be successful/ Objective : The aim of this research was to determine the acceptance of stunted toddlers who were given haruan fish formula and chicken formula Method: This type of research is descriptive, case study research on stunted toddlers by measuring the acceptability of haruan fish formula and chicken formula. The acceptability category is good if the food waste indicator is ≤ 20%. The population in this study were 11 stunted toddlers. The independent variables are: Haruan fish formula and chicken formula, the dependent variable is: acceptability. Results : The results of this study are: the most stunted toddlers are aged 13 - 24 months (54.55%). The most common gender of stunted toddlers is male (72.73%). Haruan fish formula and chicken formula made in schotel form, given to stunted toddlers for six consecutive days, found an average of less than 20% remaining in the formula. This means that food remaining less than or equal to 20% is an indicator of success.